Clinico-histopathological study of varicose vein and role of matrix metalloproteinases-1, matrix metalloproteinases-9 and tissue inhibitor of matrix metalloproteinase-1 in varicose vein formation - Bitan Naik; Mohan Kumar; Ajay Kumar Khanna; Pradeep Kumar Suman (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Varicose vein (VV) is an important cause of morbidity in the young and elderly population. Many studies of the Western country suggest that matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs have a crucial role in the pathogenesis of VV, but limited work has been done in Indian population. The aim of this study is to study detailed histology of VV and to see the expression of MMP-1, MMP-9 and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1). Materials and Methods: A total of 63 cases of VV and 10 control leg veins were included in this prospective study. Paraffin sections of VV were prepared. Hematoxylin and eosin (H and E), Masson trichrome and Verhoeff's staining were performed. Immunohistochemistry of VV was done with MMP-1, MMP-9, and TIMP-1 antibodies. Cytoplasmic expression of MMP-1, MMP-9 and TIMP-1 were graded as intense positive (++), weak/slight positive (+), and absent (−). Results: Focal intimal thickening (47.6%), increased medial thickening (73%) and fragmentation of elastin fibers (84.1%) were the major histological changes noted in H and E and special stained sections. MMP-1 expression increased in all layers of VV in 58 cases (92.1%) as compared to control veins. As compared to the control veins, intimal and adventitial expression of MMP-9 were increased in 31 (49.2%) and 40 (63.5%) cases, respectively. Expression of TIMP-1 was absent in both the varicose and the control veins. Conclusion: Increased expression of MMP-1 and MMP-9 suggests they have an important role in the pathogenesis of VV.